2011
DOI: 10.3171/2010.9.jns10646
|View full text |Cite
|
Sign up to set email alerts
|

Results with judicious modern neurosurgical management of parasagittal and falcine meningiomas

Abstract: Importantly, these data provide a more modern estimate of the expected outcomes that can be obtained with treatment of these tumors, in which a combination of image guidance, advanced microsurgical tools, and conformal radiation treatments is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 19 publications
(31 reference statements)
2
72
0
3
Order By: Relevance
“…Vein sacrifice can therefore be safely performed only by combining temporary clipping and function monitoring. 3 With regard to the outcome data for our strategy, larger series have reported a radical resection rate of 81%-93%, 4,14,19,22 quite similar to the one presented in our study (86%). Our data are similar to those published in the literature also when focusing on the pattern of SSS invasion: resection rates of meningiomas invading or not invading the SSS have been reported in 62% and 96% of cases, respectively, in the literature, 22 and in 71% and 100%, respectively, in our experience.…”
Section: Comparison Of Our Data With Relevant Literaturesupporting
confidence: 78%
See 2 more Smart Citations
“…Vein sacrifice can therefore be safely performed only by combining temporary clipping and function monitoring. 3 With regard to the outcome data for our strategy, larger series have reported a radical resection rate of 81%-93%, 4,14,19,22 quite similar to the one presented in our study (86%). Our data are similar to those published in the literature also when focusing on the pattern of SSS invasion: resection rates of meningiomas invading or not invading the SSS have been reported in 62% and 96% of cases, respectively, in the literature, 22 and in 71% and 100%, respectively, in our experience.…”
Section: Comparison Of Our Data With Relevant Literaturesupporting
confidence: 78%
“…22,23 A recent MEDLINE review of the literature on parasagittal meningiomas published over the last 60 years reported no evidence that aggressive management presents an advantage in terms of recurrence rate. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The recurrence rate was 8.6% after a mean follow-up of 5.9 years. In a study of 55 patients with parasagittal or falcine meningiomas and partial occlusion of the superior sagittal sinus who were not good candidates for radiosurgery, Sughrue et al 47 reported subtotal resection for 22 cases in which sinus involvement was extensive. Among these cases were 8 patients who underwent radiosurgery for residual disease.…”
Section: Conservative Managementmentioning
confidence: 99%
“…A staged approach (resection followed by radiosurgery to treat the residual meningioma) as described by Dr. Kondziolka and others seems reasonable for those patients with larger PSPF meningiomas next to a patent sinus or large draining vein; it is clear that the goal in contemporary management of disease in such patients need not be a Simpson Grade I resection. 4 Resection of tumor invading the superior sagittal sinus and reconstruction of the sinus seem less necessary given the efficacy of radiosurgery.…”
Section: Department Of Neurological Surgery University Of Virginia mentioning
confidence: 99%